ASEAN-KOREA FREE TRADE AREA (AKFTA) : PERDAGANGAN LIQUEFIED NATURAL GAS (LNG) INDONESIA-REPUBLIK KOREA (2012-2017) - Hutapea, Theresia Legia; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to describe the trade of LNG between Indonesia and Republic of Korea in 2012-2017. Both of Indonesia and Republic of Korea are the members of AKFTA (ASEAN-Korea Free Trade Area). One of the purposes of forming AKFTA is to liberalize the trade between Southeast Asia countries and Republic of Korea. LNG as the new natural resources is one of the main trade product of Indonesia to Republic of Korea. Overall, this research is talk about the trade of LNG of Indonesia to Republic of Korea under the scheme of AKFTA. This research uses the perspective of liberalism and the theories of proportion factor and the role of government in the economy. This research used descriptive qualitative research methods which the research data obtained through literature review from official document, books, etc.This result indicates that the trade of LNG of Indonesia to Republic of Korea in 2012-2017 is in a constant decrease. The main factors of this constant decrease are natural resources factor, employee factor, and government policy factor. Keywords: AKFTA, Liquefied Natural Gas Trade, Proportion Factor.